2019
DOI: 10.1016/j.nano.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine nanoparticles displaying recombinant Ebola virus glycoprotein for induction of potent antibody and polyfunctional T cell responses

Abstract: The recent outbreaks of Ebolavirus (EBOV) in West Africa underscore the urgent need to develop an effective EBOV vaccine. Here, we report the development of synthetic nanoparticles as a safe and highly immunogenic platform for vaccination against EBOV. We show that a large recombinant EBOV antigen (rGP) can be incorporated in a configurational manner into lipid-based nanoparticles, termed interbilayer-crosslinked multilamellar vesicles (ICMVs). The epitopes and quaternary structure of rGP were properly maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…Notably, previous studies have shown that subunit vaccines based on eGP were able to protect vaccinated mice against lethal EBOV challenge [29,30]. Bazzill, J. D. et al [31] proved that a recombinant EBOV antigen (eGP) incorporated into lipid-based nanoparticles could efficiently generate germinal center B cells and polyfunctional T cells while eliciting robust neutralizing antibody responses. Furthermore, the absence of the signal sequence and transmembrane domain facilitated protein expression [10].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, previous studies have shown that subunit vaccines based on eGP were able to protect vaccinated mice against lethal EBOV challenge [29,30]. Bazzill, J. D. et al [31] proved that a recombinant EBOV antigen (eGP) incorporated into lipid-based nanoparticles could efficiently generate germinal center B cells and polyfunctional T cells while eliciting robust neutralizing antibody responses. Furthermore, the absence of the signal sequence and transmembrane domain facilitated protein expression [10].…”
Section: Discussionmentioning
confidence: 99%
“…This role makes antibodies targeting this antigen very effective at preventing infection. Bazzill et al developed lipid‐based NPs called interbilayer crosslinked multilamellar vesicles (ICMVs) . These ICMVs were engineered to display EBOV GP in a controlled orientation ( Figure a).…”
Section: Biomaterials Provide Control Over the Molecular Properties Omentioning
confidence: 99%
“…a) Trimer proteins self‐assemble as on the surface of a virus in the native orientation. Reproduced with permission . Copyright 2019, Elsevier.…”
Section: Biomaterials Provide Control Over the Molecular Properties Omentioning
confidence: 99%
See 2 more Smart Citations